Morphology and function of the hyoid apparatus of fossil xenarthrans (mammalia) - Pérez, Leandro Martín (2010)
The analysis of the hyoid apparatus of fossil xenarthrans provides insight on the form of the tongue and its function in food intake and intraoral processing. The hyoid apparatus of xenarthrans is notable for fusion among its elements. The presence of a V-bone, a complex consisting of fused basihyal and thyrohyal bones, is a consistent and probably synapomorphic feature of xenarthrans. Fusion of other elements is variable in fossil xenarthrans. Most fossil sloths retain independent elements, as in living dasypodids and mammals generally. Among nothrotheriids, the elements are slender and their articular surfaces indicate considerable mobility, and the relatively long and horizontal orientation of the geniohyoid muscle suggests considerable tongue protrusion. Among mylodontines, such as Paramylodon and Glossotherium, the elements indicate relatively mobile articulations, except between the stylo- and epihyals. The relatively posterior placement of the apparatus and the length and alignment of the geniohyoid muscle indicate considerable capacity for tongue protrusion. Scelidotherium, however, had rigidly articulated stylohyal and epihyal, and the apparatus lies farther anteriorly, which together with the elongated, steeply inclined mandibular symphysis, indicates a relatively shorter geniohyoid muscle and thus more limited capacity for tongue protrusion. A similar situation is indicated for Megatherium, casting doubt on the classical reconstruction of this sloth as having a long prehensile tongue. Among cingulates Prozaedyus resembles living dasypodids, indicating considerable tongue protrusion important in food acquisition and intake. More extensive fusion of hyoid elements occurs in the cingulates Glyptodon and Proeutatus, in which the stylohyal and epihyal at least, are fused into a single element termed the sigmohyal. The presence of this element supports recent proposals of a sister-group relationship between glyptodonts and eutatines. The rigidity of the apparatus suggests limited tongue protrusion, but the tongue, in glyptodonts at least, was a powerful structure important for intraoral manipulation of food.